2022
DOI: 10.1161/jaha.121.024140
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Citizen Responders to Out‐of‐Hospital Cardiac Arrest During the COVID‐19 Outbreak in Denmark 2020

Abstract: Background Little is known about how COVID‐19 influenced engagement of citizen responders dispatched to out‐of‐hospital cardiac arrest (OHCA) by a smartphone application. The objective was to describe and analyze the Danish Citizen Responder Program and bystander interventions (both citizen responders and nondispatched bystanders) during the first COVID‐19 lockdown in 2020. Methods and Results All OHCAs from January 1, 2020, to June 30, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…Our work complements data from other regions where the willingness of bystanders to provide CPR did not waver during the COVID-19 pandemic. [3] , [20] , [21] , [22] …”
Section: Discussionmentioning
confidence: 99%
“…Our work complements data from other regions where the willingness of bystanders to provide CPR did not waver during the COVID-19 pandemic. [3] , [20] , [21] , [22] …”
Section: Discussionmentioning
confidence: 99%
“…コロナ禍となり3密の回避が推奨され,人との接触をなるべく避けることや外出が制限されたことにより,自宅で孤立していることが多くなるという生活様式に変化がもたらされた。このため,心停止の目撃が減少し 9), 10),バイスタンダーCPRが減少したと報告されている 6), 11)。しかし,Tanakaら 12)の日本の高齢者での検討やシンガポールの検討 13)では自宅にいることが多く,家族と生活していることが多くなったためか心停止の目撃はむしろ増加したとの報告もある。バイスタンダーCPRの減少に関しては3密を避けるために傷病者に近づかない心理が多く働いたと推測されるが,胸骨圧迫のみの蘇生の普及などのため増加したとの報告もある 12), 14), 15)。Navolokinaら 16)は,小児の報告でバイスタンダーCPRが減っていないのは,胸骨圧迫のみの心肺蘇生法の普及の成果だとしている。今回の検討では,心停止の目撃はコロナ禍でも変わらず,バイスタンダーCPRはより多く実施されていた。当地域では,自宅で家族と暮らしている人も多いため外出自粛により家族で自宅で過ごしていることが多くはなったが,部屋で隔離を意識していたため心停止の目撃は多くならず,バイスタンダーは近親者であることが多いため,CPRは抵抗なくしやすくなり施行率が増加したと考える。…”
Section: 考  察unclassified
“…2). Although several observational studies have found arrival of volunteer responders associated with increased bystander CPR and early defibrillation [27][28][29]30 & ,31-33], only two randomized controlled trials of volunteer responder programmes exist [34,35]. The first trial investigated the effect of adding volunteer responders to the standard EMS response (without AED retrieval) and found increased bystander CPR rates (primary outcome) but no significant improvements in 30-day survival [34].…”
Section: Volunteer Responder Programs Using On-site Automated Externa...mentioning
confidence: 99%